1991
DOI: 10.1136/adc.66.5.617
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of gastro-oesophageal reflux in cystic fibrosis.

Abstract: Abnormal degrees of gastro-oesophageal reflux (GOR) were detected by 24 hour intraoesophageal pH measurement in 12 of 14 children (mean age 7-9 years; range 5 months-16 years) affected by cystic fibrosis and complaining of symptoms suggesting GOR. These patients underwent combined recording of distal oesophageal motility and intraluminal pH in order to investigate mechanisms of GOR. Inappropriate lower oesophageal sphincter relaxation was the most common mechanism of reflux in all patients. Other mechanisms (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
29
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(30 citation statements)
references
References 16 publications
0
29
1
Order By: Relevance
“…A slumped position raises intra-abdominal pressure and this is one mechanism that may induce GOR [11]. Transient relaxations of the lower oesophageal sphincter (LOS), a cause of GOR, especially in CF [12], are also more frequent when sitting [13]. A head-downward tipped position may prevent GOR as intra-abdominal pressure falls and intrathoracic pressure rises, thus actually reducing the adverse gradient across the LOS which would otherwise favour reflux [14].…”
Section: Discussionmentioning
confidence: 99%
“…A slumped position raises intra-abdominal pressure and this is one mechanism that may induce GOR [11]. Transient relaxations of the lower oesophageal sphincter (LOS), a cause of GOR, especially in CF [12], are also more frequent when sitting [13]. A head-downward tipped position may prevent GOR as intra-abdominal pressure falls and intrathoracic pressure rises, thus actually reducing the adverse gradient across the LOS which would otherwise favour reflux [14].…”
Section: Discussionmentioning
confidence: 99%
“…Changes in management styles therefore cannot be attributed to changes within the population, and are not a reflection of underlying changes within the groups. 18 (Button et al, 1997(Button et al, , 1998Cucchiara et al, 1991;Malfroot and Dab, 1991). Exacerbation of symptoms in a child with ENT pathology, or discomfort in children with gastrostomies or venous access implants in a head-down position may also be a factor.…”
Section: Discussionmentioning
confidence: 94%
“…It has been suggested that micro-aspiration might play an important role in the pathophysiology of reflux-related respiratory disorders, probably in addition to other mechanisms like the esophagobronchial reflex pathway and bronchial hypersensitivity. There are several protective mechanisms against aspiration, such as esophageal clearance, which has been suggested to be altered in the CF population, and reflex closure of the UES and/or vocal cords [2,16,17]. In healthy subjects, gastric aspirate may be cleared very rapidly from the lungs.…”
Section: Discussionmentioning
confidence: 98%